Standardization of Hpx Spool for Lead Time Reduction of String Test - Venkatesh, S.; .Balasubramani, S; Venkataramanan, S.; Gokulraj, L.; kumar, P.Ganesh (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Time is the most precious thing. In today’s competitive business world, companiesrequire small lead times, low costs and high customer service levels to survive. Because of this companies have become more customers focussed. The result is that companies have beenputting in significant effort to reduce lead times. Engineers are not only meant for design andmanufacturing, they must know how to work with time, cost and quality of product effectively and efficiently. So, engineers are also responsible for time management. Time management can be carried out in any section of the industry and can also be carried out in testing section of pump industry. The main objective of our project is to reduce the lead time taken for carrying out the string test, which is being currently carried out in centrifugal pump testing section of industry. Standardization of HPX spools is the best way to reduce lead time of pump testing. Hence aflexible bellow is introduced in between spool connected to pump and discharge pipe of test bed.Currently the process is carried out by using rigid spool to perform the string test, which makesadjustment of length impossible. This will eventually increase the lead time and incurs loss to theindustry. We are introducing a flexible bellow between spool and discharge pipe of test bedwhich reduces the setting time of string test. This advancement helps to adjust the length of thespool between discharge pipe of test bed and the discharge pipe of pump. So that variety of pumps can be tested without replacing a new spool every time. This is an improvement whencompared to traditional process. Lead time has been reduced from 5 hours to 1 hour byimplementing the above suggested method.